(untitled) (American Journal of Islam and Society, 2010)
The Society for Critical Exchange held its first Winter Theory Institute from 11-14 February 2010 at the University of Houston-Victoria, located in Victoria, Texas. Eleven scholars from a variety of disciplines and from across the United States came together to present and discuss their current work on questions regarding the affect terror and terrorism are having on education in higher education. The participants presented their work by turn, and all took part in the intense two days fully devoted to the discussions. Some of the questions we hoped to address included the following: How have institutions of higher learning responded to the specter of terror? How should academe respond? What is our professional role in a terroristic world? ...